Implementing an Extention to The Technology Acceptance Model (TAM) to Evaluate User Acceptance of Identitas Kependudukan Digital (IKD) - Wijanarko, Andang; Siregar, Michael Exaudi; Andreswari, Desi (Indonesian Journal of Computer Science and Engineering, 2024)
The objective of this study is to assess user acceptance and the factors that impact the adoption and usage of the Identitas Kependudukan Digital (IKD) application. Several significant technological obstacles arose during the implementation of IKD. Additional investigation is required to ascertain user satisfaction with applications that employ the technology acceptance model (TAM) technique. This technique combines an important aspect, specifically security. The research sample consisted of 100 participants from Bengkulu City who had used the IKD application. The data was analyzed using the Structural Equation Modeling-Partial Least Squares (SEM-PLS) methodology. The study's findings indicate that the acceptance status of IKD application users in Bengkulu city is 4.42, which corresponds to the level of agree. This suggests that the citizens of Bengkulu city have effectively adopted the IKD application. The SEM-PLS approach produced analytical data that demonstrate five factors that influence users' use of the IKD application: perceived usefulness, perceived ease of use, security, attitude towards usage, and behavioral intention to use.